Etika Politik: Perspektif Mahasiswa Terhadap Perilaku Politik Pilkada Sumatera Utara Tahun 2018 - Siregar, Muhammad Nuh; Maraimbang, Maraimbang (Prodi Tata Negara (Siyasah) IAIN Langsa, 2024)
The focus of this study is to determine the forms of deviation in political behavior of participants in the 2018 North Sumatra Regional Election in terms of Islamic political ethics, according to students of the Islamic Political Thought Study Program at Universitas Islam Negeri Sumatera Utara (UINSU). This research approach is descriptive and qualitative. Data was collected through observation and in-depth interviews with five students of Islamic political thought who were selected purposefully. The results of the research revealed that students assessed that there were many irregularities in the political behavior of participants in the 2018 North Sumatra simultaneous regional elections. Indications revealed include the practice of money politics, bureaucratic politicization, threats and intimidation, and black campaigns. According to the students, this deviation in behavior contradicts the teachings of the Koran and Hadith, which serve as standards for all Muslims. Students studying Islamic political thought also believe that the deviations in behavior observed during the recent regional elections in North Sumatra are an obvious indication of the decline in religious values and the weakening of faith among both the political elite and society as a whole, which is increasingly embracing materialistic ideals. According to this perspective, this article affirms that political ethics directs the exercise of power in the state to align with democratic, honest, and ethical values.